An Evaluation of the Impact of Australia's First Community Notification Scheme - Whitting, Laura (Psychiatr Psychol Law, 2016)
In 2012, one Australian state became the first jurisdiction in Australasia to introduce a scheme that allows information about registered sex offenders to be released to the public. This study seeks to better understand the impact of the scheme from the perspective of the police. An analysis of interviews with police officers responsible for the administration of the scheme is supplemented with an analysis of official data relevant to its implementation. The results provide little evidence that the concerns voiced by the police about the introduction of community notification have been realised. There is no consistent view that it has significantly increased the workload of the police responsible for its management, impacted adversely on offenders’ psychological well-being, led to vigilantism or resulted in offenders’ non-compliance with reporting obligations. The findings of this study may usefully inform the development of policy and practice in places that are considering introducing similar policies.